The Molecular Regulation of Carbon Sink Strength in Grapevine (Vitis vinifera L.) - Li, You-Mei; Forney, Charles; Bondada, Bhaskar; Leng, Feng; Xie, Zhao-Sen (Frontiers in Plant Science, 2021)
Sink organs, the net receivers of resources from source tissues, provide food and energy for humans. Crops yield and quality are improved by increased sink strength and source activity, which are affected by many factors, including sugars and hormones. With the growing global population, it is necessary to increase photosynthesis into crop biomass and yield on a per plant basis by enhancing sink strength. Sugar translocation and accumulation are the major determinants of sink strength, so understanding molecular mechanisms and sugar allocation regulation are conducive to develop biotechnology to enhance sink strength. Grapevine (Vitis vinifera L.) is an excellent model to study the sink strength mechanism and regulation for perennial fruit crops, which export sucrose from leaves and accumulates high concentrations of hexoses in the vacuoles of fruit mesocarp cells. Here recent advances of this topic in grape are updated and discussed, including the molecular biology of sink strength, including sugar transportation and accumulation, the genes involved in sugar mobilization and their regulation of sugar and other regulators, and the effects of hormones on sink size and sink activity. Finally, a molecular basis model of the regulation of sugar accumulation in the grape is proposed.